Effects of different conservational regimes on edaphic factors changes in “Striletskiy step” reserve (Russia) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
A method of computer synphytoindication was applied to clarify the impact of grazing, haying and total reservation on changes in ecotopes. The magnitude of some edaphic factors (humidity of soils, nitrogen and acid regimes) are justified by trustworthy differences on plots with different conservational regimes.
Keywords: meadow steppe, edaphic ecological factors, phytoindication, conservational regimes.